2016
DOI: 10.1186/s13104-016-2197-x
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of rheumatology research in the Arab countries

Abstract: BackgroundThe Arab world has seen an increase in the burden of musculoskeletal diseases. No bibliometric studies have characterized rheumatology research in the Arab world. This study evaluates the productivity and impact of rheumatology research in the Arab world.MethodsWe searched the Web of Science Core Collection for rheumatology publications, from 1976 to 2014, for each of the Arab League (AL) countries, North America, Europe and Asia. For the AL countries, the overall trend of publications and citations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
1
10
0
3
Order By: Relevance
“…In addition, results of the study indicated that the majority of IoT researchers in the Arab world collaborated not only with other researchers within the Arab countries but also with researchers from around the world such as France, the USA, and UK. The results are in line with the previous studies [18][19][20] . Similarly, authors of the top ten universities demonstrated having 95 per cent collaborations with other scholars and scientists with locally and internationally.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, results of the study indicated that the majority of IoT researchers in the Arab world collaborated not only with other researchers within the Arab countries but also with researchers from around the world such as France, the USA, and UK. The results are in line with the previous studies [18][19][20] . Similarly, authors of the top ten universities demonstrated having 95 per cent collaborations with other scholars and scientists with locally and internationally.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, Tunisia and Sudan had the highest research productivity in the field leishmaniasis. Previous bibliometric studies have assessed different issues in biomedical field in the Arab world [21,59,61,66,[79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of scientific publications constitutes a fundamental link in the research process and therefore it has become a tool that allows to evaluate the generation, evolution and impact of knowledge in the environment (Rueda-Clausen, Villa-Roel and Rueda-Clausen, 2005; Escorcia, 2008) providing a macroscopic overview of large amounts of academic literature (van Nunen, Li, Reniers & Ponnet, 2007). This activity has been called bibliometrics, which is a part of scientometrics, it is multidisciplinary and is defined as the application of mathematical and statistical methods to analyze the nature and course of scientific publications (Merigó, 2016;Campos, 2007), it can reveal the latest advances, research directions and main topics in a particular field of research (Wang, Pan, Ke, Wang & Wei, 2014), as well as the identification of current gaps in a given research discipline, both in terms of content and geographically (Gall, Nguyen & Cutter, 2015), which allows researchers to orient future lines of research towards specific fields (Bayoumy, Dargham and Arayssi, 2016). Nowadays, a large number of bibliometric studies are carried out (Soosaraei, Akbar, Fakhar & Ziaei, 2018).…”
Section: Methodsmentioning
confidence: 99%